2015
DOI: 10.1038/hdy.2015.89
|View full text |Cite|
|
Sign up to set email alerts
|

Ancestral whole-genome duplication in the marine chelicerate horseshoe crabs

Abstract: Whole-genome duplication (WGD) results in new genomic resources that can be exploited by evolution for rewiring genetic regulatory networks in organisms. In metazoans, WGD occurred before the last common ancestor of vertebrates, and has been postulated as a major evolutionary force that contributed to their speciation and diversification of morphological structures. Here, we have sequenced genomes from three of the four extant species of horseshoe crabs-Carcinoscorpius rotundicauda, Limulus polyphemus and Tach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
131
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(146 citation statements)
references
References 81 publications
(105 reference statements)
15
131
0
Order By: Relevance
“…We also analysed four different Daphnia magna transcripts of inotocin receptors, which are probably the result of alternative splicing since these sequences are almost identical except for minor deletions/insertions in intracellular loop 3 as well transmembrane domains 3 and 5. The presence of multiple copies in some of the species could be explained by whole genome or large scale duplication events, which have been reported for Limulus polyphemus 2627, Ixodes scapularis 28, Calanus finmarchicus 29 and Strigamia maritima 30. Local and whole genome duplication and deletion events during vertebrate evolution led to different number of gene copies (two or more) of oxytocin/vasopressin receptors and precursors within distinct vertebrate species3132.…”
Section: Discussionmentioning
confidence: 89%
“…We also analysed four different Daphnia magna transcripts of inotocin receptors, which are probably the result of alternative splicing since these sequences are almost identical except for minor deletions/insertions in intracellular loop 3 as well transmembrane domains 3 and 5. The presence of multiple copies in some of the species could be explained by whole genome or large scale duplication events, which have been reported for Limulus polyphemus 2627, Ixodes scapularis 28, Calanus finmarchicus 29 and Strigamia maritima 30. Local and whole genome duplication and deletion events during vertebrate evolution led to different number of gene copies (two or more) of oxytocin/vasopressin receptors and precursors within distinct vertebrate species3132.…”
Section: Discussionmentioning
confidence: 89%
“…Both the busco and mapping rate tests showed that this assembled genome of T. tridentatus is a high quality reference genome of horseshoe crab. In addition, the quality of our assembled chromosome‐level genome is obviously higher than the released horseshoe crab versions (Supporting Information Table S6; Kenny et al, ; Nossa et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…WGD occurred twice at the base of vertebrates [13,14], once in the stem lineage of teleost fish [15][16][17], one or more times in cyprinid fish [18], once in salmonid fish [19], two or more times in chelicerates [20,21] and once in rotifers [22]; undoubtedly more cases will be discovered. However, a clear finding is that gene loss is extensive after WGD, possibly reaching as high as 85% of duplicates in some cases [23].…”
Section: Gene Numbers: Up and Down In Evolutionmentioning
confidence: 99%